2011
DOI: 10.1186/1471-2156-12-96
|View full text |Cite
|
Sign up to set email alerts
|

Association of an ACSL1 gene variant with polyunsaturated fatty acids in bovine skeletal muscle

Abstract: BackgroundThe intramuscular fat deposition and the fatty acid profiles of beef affect meat quality. High proportions of unsaturated fatty acids are related to beef flavor and are beneficial for the nutritional value of meat. Moreover, a variety of clinical and epidemiologic studies showed that particularly long-chain omega-3 fatty acids from animal sources have a positive impact on human health and disease.ResultsTo screen for genetic factors affecting fatty acid profiles in beef, we initially performed a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 66 publications
5
37
1
Order By: Relevance
“…PRKG1 was identified as one of 20 genes associated with milk fatty acid traits in Holstein (Li et al 2014), and its functions include calcium channel regulator activity and cGMP-dependent protein kinase activity. This study also identified ACSL1 associated with the milk fatty acid traits (Li et al 2014) and supported by other studies (Widmann et al 2011;Gao et al 2013;Weber et al 2013). Other identified genes in our current study are involved in somatic cell score and meat quality traits, such as GRIN2B (Wu et al 2014) and PLXNA4 (Strillacci et al 2014).…”
Section: Strs Overlap With Regions Under Selection Predicted Based Onsupporting
confidence: 68%
“…PRKG1 was identified as one of 20 genes associated with milk fatty acid traits in Holstein (Li et al 2014), and its functions include calcium channel regulator activity and cGMP-dependent protein kinase activity. This study also identified ACSL1 associated with the milk fatty acid traits (Li et al 2014) and supported by other studies (Widmann et al 2011;Gao et al 2013;Weber et al 2013). Other identified genes in our current study are involved in somatic cell score and meat quality traits, such as GRIN2B (Wu et al 2014) and PLXNA4 (Strillacci et al 2014).…”
Section: Strs Overlap With Regions Under Selection Predicted Based Onsupporting
confidence: 68%
“…The data strongly suggested that differences in the flavor of grass and grain fed beef is mainly due to differences in fat level rather than due to inherent grass or grain flavors (Frank et al , 2016). Refinement of animal production and feeding strategies to optimize the composition of IMF and enhance sensory properties of beef will present new opportunities for producers of marbled beef (Barendse, 2014; Scollan et al , 2014; Widmann et al , 2011). …”
Section: Opportunities For Improving Meat Qualitymentioning
confidence: 99%
“…Many Asian consumers prefer moderate amounts of IMF in the meat they purchase, whereas visible fat is unpopular with Western (e.g., Europe, Australia) consumers. The amount of IMF within beef muscle varies widely depending on animal breed or genetics (Barendse, 2014; Hocquette et al , 2014; Widmann et al , 2011), the nutrition system (pasture or grain) (Duckett et al , 2013; Sithyphone et al , 2011; Van Elswyk and McNeill, 2014), animal maturity and weight (Duckett et al , 2014; Frank et al , 2016), primal (Pavan and Duckett, 2013) and other factors. Marbling describes the small flecks of visible fat deposited between individual muscle fiber bundles.…”
Section: Introductionmentioning
confidence: 99%
“…The g.28381 G>A was in intron 3, and g.28265 G>C, g.28470 T>C, and g.28672 G>A were silent mutations found in exons 3, 4, and 5, respectively. Since IMF deposition and the fatty acid profiles of beef affect meat quality (Widmann et al, 2011), and the gene expression abundance of FATP1 has been shown to exhibit significant positive correlations (P < 0.05) with IMF content in LM , it was hypothesized that this mutation may influence FATP1 protein synthesis. However, this needs to be validated in future studies.…”
Section: Polymorphisms Of Fatp1 Via Sequencingmentioning
confidence: 99%